Leveraging Mobile Technology to Enhance Agricultural Extension Services: A Review - Yashabh,; Naman,; , Asma Fayaz; , Munish Kaundal (Archives of Current Research International, 2025)
The accelerated growth of mobile technology and digital applications has initiated a revolutionary shift in agricultural extension services, especially in developing countries where agriculture is the pillar of rural economies. The conventional extension services, characterized by field visits and on-site consultations, were mostly hampered by time, distance, and resource limitations. This review examines the impact of mobile apps on Agriculture Extension Services. Mobile applications have become a game-changer by giving farmers real-time access to critical agricultural information directly on their smart phones. Mobile apps provide weather forecasts, pest and disease identification, market price information, expert advisory, and even financial services, all of which lead to enhanced farm productivity and better decision-making. By means of mobile-based advisory platforms such as Kisan Call Center in India and M-Kilimo in Kenya, farmers can access the advice of experts without having to wait for physical visits by extension officers. The inclusion of mobile banking services within agriculture apps has strengthened the financial inclusion of farmers further, enabling them to obtain credit, receive secure payments, and invest in quality inputs. Through the closure of the information gap, mobile apps enable smallholder farmers to make effective plans, avoid wastage of inputs, increase yields, and get better access to markets, thereby increasing their incomes and livelihoods. Poor internet coverage, low digital literacy, the exorbitant price of smart phones, and limited localized content are some of the significant hindrances that bar many farmers from enjoying the full benefits of these technologies. The overcoming of these obstacles demands combined inputs from governments, private tech companies, and agriculture organizations to facilitate rural connectivity, offer subsidized devices, and conduct inclusive training packages to raise the digital capacities of farmers. All in all, the expanding interface of mobile applications with extension services in agriculture promises enormous opportunities for transforming farm management, improving the sustainability of agriculture, and enriching smallholder farmers' livelihoods through access to more affordable, effective, and farmer-centered extension services. Overall, mobile apps have great potential to make agriculture more modern, efficient, and sustainable. By giving farmers quick access to the right information, these apps help them make better decisions, improve their crops, and earn more money. With the right support, mobile apps can play a big role in improving the lives of farmers and making agriculture better for the future.